Deleterious effects of mercury contamination on immunocompetence, liver function and egg volume in an antarctic seabird - Ibañez, Andres Esteban (2023)
Mercury (Hg) is a globally important pollutant that can negatively impact metabolic, endocrine and immune systems of marine biota. Seabirds are long-lived marine top predators and hence are at risk of bioaccumulating high Hg concentrations from their prey. Here, we measured blood total mercury (THg) concentrations and relationships with physiology and breeding parameters of breeding brown skuas (Stercorarius antarcticus) (n = 49 individuals) at Esperanza/Hope Bay, Antarctic Peninsula. Mean blood THg concentrations were similar in males and females despite the differences in body size and breeding roles, but differed between study years. Immune markers (hematocrit, Immunoglobulin Y [IgY] and albumin) were negatively correlated with blood THg concentrations, which likely indicates a disruptive effect of Hg on immunity. Alanine aminotransferase (GPT) activity, reflecting liver dysfunction, was positively associated with blood THg. Additionally, triacylglycerol and albumin differed between our study years, but did not correlate with Hg levels, and so were more likely to reflect changes in diet and nutritional status rather than Hg contamination. Egg volume correlated negatively with blood THg concentrations. Our study provides new insights into the sublethal effects of Hg contamination on immunity, liver function and breeding parameters in seabirds. In this Antarctic species, exposure to sublethal Hg concentrations reflects the short-term risks which could make individuals more susceptible to environmental stressors, including ongoing climatic changes.